Business Cycles and Growth of South African Steel Manufacturing Industry - Tsebe, Andretta (Journal of Economics and Behavioral Studies, 2022)
The paper studies the relationship between the South African business cycle and the performance of the steel industry. The analysis was conducted by first providing a brief bibliometric review of the definitions used for business cycles in literature. From this initial analysis, emerging themes were used to define the narrative literature review on the relationship between business cycles, economic growth, and supply-demand of the steel industry. Findings from the review, indicate a binary relationship between economic growth and steel industry output. It is recommended that future studies be done on quantitative analysis of the binary and ternary relationships between economic growth and other primary manufacturing industries in South Africa.